Characterization of cadmium accumulation mechanism between eggplant (Solanum melongena L.) cultivars - Shen, Chuang; Huang, Ying-Ying; Liao, Qiong; Huang, Bai-Fei; Xin, Jun-Liang; Wang, Luo; Fu, Hui-Ling (Frontiers in Plant Science, 2023)
Excessive cadmium (Cd) accumulation in vegetables due to farmland pollution constitutes a serious threat to human health. As a major vegetable, eggplant has a tendency to accumulate Cd. In this study, we investigated the mechanisms of Cd accumulation ability in eggplant through physiological characteristics and comparative transcriptome analysis based on a high-Cd (BXGZ) and a low-Cd (MYQZ) cultivar. It was revealed that MYQZ enhanced pectin methylesterase (PME) activity and lignin content in the root cell wall by up-regulating the expression levels of PME, cinnamyl-alcohol dehydrogenase and peroxidase (PODs), which facilitated the fixation of Cd in the root cell wall. Higher levels of cysteine and glutathione (GSH) contents and genes associated with sulfur metabolism in MYQZ are expected to help reduce Cd toxicity. Besides, Cd translocation was inhibited by compartmentalizing Cd within the vacuole through the higher expression of ATP-binding cassette transporters (ABCs), cation exchanger (CAX), and metal tolerance protein (MTPs) in the root of MYQZ. In contrast, BXGZ featured a more developed root system and higher transpiration rate through up-regulation of root development-related and water channel protein genes and stomatal properties, thereby enhancing its Cd uptake and translocation to shoot.